2007
DOI: 10.1016/j.amjmed.2006.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, Vitamins and Respiratory Tract Infections

Abstract: Chubak et al. 1 reported that moderate intensity exercise training reduced common cold incidence but had no effect on the total incidence of upper respiratory infections. As a motivation for the trial, they cited two randomized 3-4 month trials 2,3 which, however, did not find statistically significant effect on upper respiratory infection incidence from moderate exercise, but the studies were small (N 36).In their paper, Chubak et al. failed to refer to our study analyzing the relation between physical activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
83
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 5 publications
1
83
1
Order By: Relevance
“…These findings with clinically relevant outcomes thus contradict the surrogate-based proposal by Bruno et al that smokers would benefit of higher vitamin E intakes and it would seem necessary for them to consume at least 15 mg/day of vitamin E [3]. Furthermore, the current US RDA recommendation level for vitamin E, 15 mg/day, is not based on any clinically relevant outcome either and is arbitrary [6]. The divergence in the effects of vitamin E supplementation in the ATBC Study cohort indicates that caution should be maintained in any proposals that people should increase their consumption of vitamin E until its effects are better understood.…”
mentioning
confidence: 68%
“…These findings with clinically relevant outcomes thus contradict the surrogate-based proposal by Bruno et al that smokers would benefit of higher vitamin E intakes and it would seem necessary for them to consume at least 15 mg/day of vitamin E [3]. Furthermore, the current US RDA recommendation level for vitamin E, 15 mg/day, is not based on any clinically relevant outcome either and is arbitrary [6]. The divergence in the effects of vitamin E supplementation in the ATBC Study cohort indicates that caution should be maintained in any proposals that people should increase their consumption of vitamin E until its effects are better understood.…”
mentioning
confidence: 68%
“…They discussed the technical aspects of certain studies, but in most cases they did not present the original results, thereby hampering the reader in drawing his or her own conclusions about the trial results. 6,7 They uncritically accepted Karlowski et al's placebo effect explanation, 2 although careful reading of the report would have shown that it is not valid. There are many further problems in the Dykes and Meier review, 3 as described elsewhere.…”
mentioning
confidence: 99%
“…[4][5][6] The authors argued that the results of their placebo controlled double-blind trial might be explained, paradoxically, by the placebo effect. However, their suggestion was based on a subgroup analysis in which they excluded 42% of recorded common cold episodes without any justification.…”
mentioning
confidence: 99%
See 2 more Smart Citations